ATTENUATION OF RETINAL DAMAGE AFTER EXPOSURE TO WHITE LIGHT BY TAURINE ASSESSED BY ELECTRORETINOGRAM AND COMET ASSAY - EMAN MOHAMED ALY; MERVAT AHMED ALY; EMAN SAAD MOHAMED (International Journal of Pharma and Bio Sciences, 2012)
The purpose of this study is to investigate the protective effect of taurine against photochemical damage in rabbit retina. Twenty seven rabbits were divided into three groups: control group (A), exposed to light without (B) and with taurine (C). Groups B and C were divided into four subgroups according to the time of exposure to white light (3, 6, 12 and 24 hr). Group C treated with taurine (4 g taurine /100 g diet) for 2 weeks before exposure to white light (2500± 100 lux). Retinal function was assessed by electroretinogram (ERG). The comet assay also was used to examine qualitative and quantitative aspects of DNA. Statistically significant reduction in a- and b - waves was apparent (p < 0.05) in group (B) that exposed to light and reach maximum reduction after 24 hr of exposure, the percentage difference was 81 % and 83 % for a-and b- waves respectively. The reduction of a-and b- wave amplitude after light exposure was attenuated by taurine intake. Also, the extent of DNA damage proportionally increased with increasing time of exposure to white light that appear in the elevated mean percentage tail DNA and tail moment that reached 6.16±0.4% and 14.2% respectively at 24 hr of exposure to white light. Taurine effect was appeared clearly by decreasing this percentage to 3.3±0.2% and 5.2% for the same group. Our results revealing the importance of taurine that played neuroprotective role in retina after exposed to white light.